2018
DOI: 10.1589/jpts.30.748
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of subcutaneous lidocaine injection in venous insufficiency: a prospective, randomized, controlled study, and new treatment protocol

Abstract: [Purpose] The purpose of this study was to evaluate the efficacy of subcutaneous injection with lidocaine in patients with chronic venous insufficiency in the early stage. [Subjects and Methods] Patients (n=50) randomized to the treatment group received subcutaneous injections from a mixture of physiological saline sterile solution and lidocaine once a week to both legs below the knee for 5 sessions. Patients in the treatment group were also given ankle pumping exercises and compression stockings throughout th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Particularly for CVD, CIVIQ-20 proved to be a useful instrument for QoL measurement. Previous studies also revealed that CIVIQ-20 questionnaire results could be correlated with clinical signs and symptoms related with CVD [ 25 ], and the score results improve after the treatment, being directly correlated with the clinical evolution [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly for CVD, CIVIQ-20 proved to be a useful instrument for QoL measurement. Previous studies also revealed that CIVIQ-20 questionnaire results could be correlated with clinical signs and symptoms related with CVD [ 25 ], and the score results improve after the treatment, being directly correlated with the clinical evolution [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium dobesilate ( 1 ) is an orally administered angioprotective agent for reducing blood, plasma, and aqueous humor hyperviscosity and microvascular hyperpermeability. Up to approximately 60% incidence in developed countries use 1 as the oral treatment for diabetic retinopathy, hemorrhoidal syndrome, and chronic venous insufficiency in the lower limbs (pain, cramps, paresthesia, edema, and stasis dermatosis). After being prescribed worldwide for many years, possible conferring benefits have been discovered including potential anticancer and antiviral effects. Additionally, recent investigations have shown that 1 is an effective therapy for COVID-19 patients because its capacity to inhibit several signaling pathways can implicate COVID-19 pathophysiology. , …”
Section: Introductionmentioning
confidence: 99%